2014
DOI: 10.1186/2047-1440-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Volume and outcome relation in German liver transplant centers: what lessons can be learned?

Abstract: BackgroundThe volume and outcome relationship for transplant procedures has become one of the major topics during discussions about consequences following the organ transplantation scandal of wait-list manipulations in Germany during the past year. Proponents of reducing the number of centers argue in favor of increasing quality at highly specialized transplant centers while disregarding the wish of patients for regionally available medical service.MethodsThe homepage of the German Organ Procurement Organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…The improved outcomes for high‐volume centers in Germany, one of the Eurotransplant countries, were recently addressed in a study by Nijboer et al . , and an editorial related to this study also suggested that there was no linear relation between outcome and center size , which was also seen in the present study. One explanation for this effect could be that when a center grows beyond the 50 transplants, there will first be a transition period from being an intermediate‐volume to a high‐volume center.…”
Section: Discussionsupporting
confidence: 76%
“…The improved outcomes for high‐volume centers in Germany, one of the Eurotransplant countries, were recently addressed in a study by Nijboer et al . , and an editorial related to this study also suggested that there was no linear relation between outcome and center size , which was also seen in the present study. One explanation for this effect could be that when a center grows beyond the 50 transplants, there will first be a transition period from being an intermediate‐volume to a high‐volume center.…”
Section: Discussionsupporting
confidence: 76%
“…Hinsichtlich der Organvergabe wäre denkbar, dass gerade Kliniken mit kleinerer Fallzahl angesichts des Mangels an Spenderorganen vor allem bei den dringlichen Indikationen berücksichtigt werden. Eine weitere Studie aus Deutschland konnte eine Mengen-Ergebnis-Beziehung bei Lebertransplantationen ebenfalls nicht überzeugend nachweisen [20], obwohl es aus der internationalen Literatur Hinweise auf bessere Behandlungsergebnisse bei höherer Leistungsmenge gibt [21,22].…”
Section: Diskussionunclassified
“…An analysis of nearly 35000 liver transplant recipients in the ELTR showed patients transplanted in centers performing 70 or more transplants/year had significantly better early outcomes compared with patients transplanted in centers performing less than 70 transplants/year. 192 Another earlier study found that outcomes were better in patients transplanted in centers performing more than 20 transplants/year versus less than 20 transplants/year, whereas, a study by Nijboer et al 193,194 did not find a clear correlation between center activity and outcomes in 24 liver transplant units in Germany. In a similar US-based study, Macomber et al 195 found lower mortality rates in higher-volume centers, with lower median length of hospital and intensive care unit stay and lower direct costs.…”
Section: Provision Of Transplant Unitsmentioning
confidence: 76%